Refraction of Hoffmann’s Traditions in the Story “Torrents of Spring” by I. S. Turgenev - Vera V. Koroleva (Два века русской классики)
The article examines the story “Torrents of Spring” (1872) by I. S. Turgenev from the point of view of the presence of Hoffmann’s traditions, manifested in the mythologization of the name of the German writer E. T. A. Hoffmann and the rethinking of the plot of his short story “Mistakes” (1820). At the same time, the article considers Hoffmann’s problems, stylistics, and imaginative system, which are presented in the form of an ideological and thematic “Hoffmann complex” that includes the following features: the technique of “playing” with the plots of other people’s works; an appeal to Hoffmann’s type of character; the mirror principle of constructing the story; and Hoffmann’s stylistics. The article concludes that I. S. Turgenev, relying on Hoffmann’s tradition, sets an ironic tone for the narrative to criticize the modern trend of imitation of fashionable literary plots and cultural patterns. Turgenev uses well- known plots in an inverted way: he makes fun of not only the literary stereotypes of the era but also the characters themselves, who live and act according to the roles they have chosen. By modeling national types, Turgenev comes to problems of a universal, all-human nature.